Genetic Basis and Molecular Mechanisms of Uveal Melanoma Metastasis: A Focus on Prognosis - Gallenga, Carla Enrica; Franco, Elena; Adamo, Ginevra Giovanna; Violanti, Sara Silvia; Tassinari, Paolo; Tognon, Mauro; Perri, Paolo (Frontiers in Oncology, 2022)
Uveal melanoma (UM) is the most frequently found primary intraocular tumor, although it accounts for only 5% of all melanomas. Despite novel systemic therapies, patient survival has remained poor. Indeed, almost half of UM patients develop metastases from micro-metastases which were undetectable at diagnosis. Genetic analysis is crucial for metastatic risk prediction, as well as for patient management and follow-up. Several prognostic parameters have been ex-plored, including tumor location, basal dimension and thickness, histopathologic cell type, vas-cular mimicry patterns, and infiltrating lymphocytes. Herein, the Authors review the available literature concerning cytogenetic prognostic markers and biochemical pathways correlated to UM metastasis development.